Actinic keratosis in vitiligo after oral PUVAsol therapy with review - Saumya Sankhwar; Sunil K Gupta (Wolters Kluwer Medknow Publications, 2018)
Abstract Vitiligo is an acquired disorder characterised by depigmentation. The etiopathogenesis is still unclear and many theories have been proposed for the same. It is believed that due to lack of protective melanin, a vitiliginous patch is more prone to photodamage by UV radiation and development of skin cancers especially following PUVASOL therapy. But, few cutaneous malignancies have been reported and even fewer cases of actinic keratoses have been reported over a vitiliginous skin. Here, we report a case of elderly female who developed actinic keratoses over longstanding sun exposed vitiliginous skin post PUVA therapy.